Influence of hydrothermal pretreatment on acidity and activity of H-GaAlMFI zeolite for the propane aromatization reaction - Choudhary, Tushar V.; Kinage, A.; Banerjee, S.; Choudhary, Vasant R. (Microporous and Mesoporous Materials, 2005)
The acidity and propane aromatization activity of H-GaAlMFI has been investigated subsequent to different hydrothermal (HT) pretreatments. Extensive degalliation of framework Ga occurred during the HT pretreatments; the framework Si/Ga ratio nearly doubled when the steam concentration was increased from 0% to 80%. The extent of degalliation and corresponding loss of strong zeolitic acidity (measured in terms of pyridine chemisorbed at 400 degrees C) was particularly severe at high (> 500 degrees C) temperatures and steam concentrations (> 40 mol%). Framework Al in the GaAlMFI zeolite was found to be very stable; the FW Si/Al ratio did not change to any appreciable extent even after severe HT pretreatments. Each of the HT pretreatment parameters (concentration of steam: 0-80%, HT temperature: 400-600 degrees C and length of HT pretreatment: 0-6 h) showed a profound influence on the propane aromatization activity. The product selectivity was, however, only mildly affected by the HT pretreatments. The following factors were found to be important for high propane aromatization activity (a) strong zeolitic acidity and (b) optimal content/dispersion of the extra-framework Ga species which are formed in situ during the HT pretreatments. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: Acidity; aromatic distribution; Ga-based zeolites; hydrothermal treatment and steam; propane aromatization

Influence of PdO content and pathway of its formation on methane combustion activity - Choudhary, Tushar V.; Banerjee, S.; Choudhary, Vasant R. (Catalysis Communications, 2005)
The methane oxidation reaction is known to induce changes in the surface structure and composition of Pd catalysts; making it extremely arduous to relate the methane oxidation activity to specific catalyst properties by conventional methods (continuous flow reactor studies). To circumvent this, methodical pulse reactor studies have been undertaken to obtain correlations between the initial methane combustion activity and the catalyst properties (Pd-0/PdO content and path of PdO formation). While the initial methane combustion activity (at 160-280 degreesC) continuously increased with increasing PdO concentration (0-100%) in the catalyst, it continuously decreased with increasing Pddegrees content (0-100%). Controlled studies were undertaken to obtain catalysts with identical PdO content by two pathways: (i) by controlled partial oxidization of Pd-0/Al2O3 and (ii) by controlled partial reduction of PdO/Al2O3. Interestingly, for a given PdO content, the catalysts obtained by partial oxidation of Pd-0/Al2O3 showed a significantly superior performance to the catalyst obtained by partial reduction of PdO/Al2O3 for all the temperatures investigated. These studies unambiguously show that along with the relative concentration of PdO, the PdO formation pathway is also critical in deciding the methane combustion activity of the catalyst. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Methane combustion; Oxidation; partially oxidized Pd-0/Al2O3; partially reduced PdO/Al2O3; Pd-0/Al2O3; PdO/Al2O3; pulse reaction of methane

CO2 reforming of methane to syngas over CoOx/MgO supported on low surface area macroporous catalyst carrier: Influence of Co loading and process conditions - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Industrial & Engineering Chemistry Research, 2006)
The effect of Co loading (5-30 wt %) and process parameters ( reduction pretreatment, reaction temperature, and space velocity) have been investigated over CoOx/MgO(5%)/SA-5205 catalyst for the CO2 methane reforming process. The Co loading had a profound effect on the methane conversion and the hydrogen selectivity ( initial and time-on-stream activity) for the unreduced catalysts. While negligible methane conversion was observed for the 5 and 10 wt % Co loading catalyst, methane conversions > 95% were obtained over the high Co loading ( 20 and 30 wt %) catalysts; hydrogen selectivity followed the same trend as methane conversion. The Co loading level had a relatively smaller influence in the case of the reduced catalysts. While the 5 wt % Co catalyst showed low methane conversion activity (< 30%), the 10 wt % Co catalyst showed methane conversion levels comparable to those of the high Co loading catalysts. The high Co loading catalysts showed an excellent time-on-stream performance for the CO2 methane reforming reaction. X-ray diffraction and temperature-programmed reduction experiments indicate that the interesting activity behavior exhibited by the catalysts is related to the different phases ( and their reducibility) present in the catalysts at different Co loadings. The hydrogen selectivity was found to decrease with decreasing reaction temperature and increasing space velocity due to the increased simultaneous occurrence of the reverse water-gas shift reaction along with the CO2 reforming reaction.

Direct oxidation of H-2 to H2O2 over Pd-based catalysts: influence of oxidation state, support and metal additives - Choudhary, Vasant R.; Samanta, C.; Choudhary, Tushar V. (Applied Catalysis A-General, 2006)
The influence of oxidation state (reduced and oxidized), support (ZrO2, Ga2O3, CeO2, SiO2, H-beta, ThO2, CeO2-ZrO2, BPO4 and Pd/Al2O3) and precious metal additives (Au, Pt, Rh and Ru) on the direct H2O2 synthesis has been investigated over Pd-based catalysts. For all the supports investigated herein, the oxidized Pd catalysts showed significantly superior H2O2 yields as compared to their reduced counterparts. The effect of the Pd oxidation state was found to be more important for determining the H2O2 yields than the particle size and surface area properties of the catalyst system. An excellent correlation was observed between the H2O2 selectivity and H2O2 decomposition activity of the oxidized Pd catalysts. The oxidized Pd catalysts showed almost an order of magnitude lower H2O2 decomposition activity than the reduced catalysts. The H2O2 yield in the H-2 to H2O2 oxidation passed through a maximum with increase in the An concentration. Although a similar effect was also observed in case of Pt, Au was found to be a superior promoter for the direct H2O2 synthesis process. Addition of Rh and Ru was found to be detrimental for the H2O2 yields; these results can be explained in terms of increased H2O2 decomposition activity and/or enhanced H-2 to H2O reaction activity in their presence. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: decomposition; direct synthesis; H2O2; metal additives; oxidation state; Pd catalysts; supports

Factors influencing decomposition of H2O2 over supported Pd catalyst in aqueous medium - Choudhary, Vasant R.; Samanta, C.; Choudhary, Tushar V. (Journal of Molecular Catalysis A-Chemical, 2006)
Since H2O2 decomposition can result in selectivity/yield loss in the direct H2O2 synthesis process from H-2 and O-2 over supported Pd catalysts, it is important to have an enhanced understanding about the factors affecting the H2O2 decomposition reaction. Herein, detailed studies have been undertaken to investigate the influence of different factors, such as (a) nature and concentration of acid in reaction medium, (b) nature and concentration of halide in presence and absence of acid in reaction medium, (c) pretreatment procedures and (d) catalyst modification by incorporation of different halides, on the H2O2 decomposition reaction over a 5% Pd/C catalyst in aqueous medium at 25 degrees C. This study has shown that the H2O2 decomposition activity is profoundly influenced by all the above factors. The effectiveness of the acids in suppressing the H2O2 decomposition activity decreased in the following order: hydroiodic acid > hydrobromic acid > hydrochloric acid >> acetic acid > phosphoric acid > sulfuric acid > perchloric acid. The ability of the acid to decrease the H2O2 decomposition activity was found to very strongly depend on the nature of its associated anion. Halides, such as iodide, bromide and chloride were particularly effective in suppressing the H2O2 decomposition activity. Oxidation pretreatment of the catalyst was found to strongly suppress its H2O2 decomposition activity, while a reduction treatment was found to promote its activity. A gradual decrease in the H2O2 decomposition activity of the catalyst was observed with each successive usage due to in situ sub-surface oxidation of Pd by H2O2. Halide incorporation either via the reaction medium or prior catalyst modification had a similar qualitative effect on the H2O2 decomposition activity. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: acid; H2O2 decomposition; H2O2 synthesis; halides; Pd catalysts; pretreatment

Methane reforming over a high temperature stable-NiCoMgOx supported on zirconia-hafnia catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Chemical Engineering Journal, 2006)
The unusually high temperature stable NiCoMgOx (Ni/Co/Mg: 1:0.2:1.2)/zirconia-hafnia catalyst has been investigated for syngas generation via the catalytic partial oxidation of methane (CPOM), oxidative steam reforming of methane (OSRM) and oxidative CO2 reforming of methane (OCRM) processes. The catalyst, even when calcined at 1400 degrees C for 4 h, showed excellent activity/selectivity for the CPOM, OSRM and the OCRM reactions. On account of its high thermal stability, hot spots in the catalyst bed and/or high temperatures prevailing at the catalyst surface during the oxy-reforming processes would have little or no effect on the catalytic activity/selectivity of the NiCoMgOx/zirconia-hafnia catalyst, thus making the catalyst suitable even for operating under adiabatic conditions. While the selectivity for CO increased considerably with increasing reaction temperature for the CPOM process, the selectivity for H-2 was affected to a much lesser extent. The selectivity for CO and H-2 in the CPOM reaction was found to decrease with increasing space velocity; the H-2 selectivity was however affected to a greater extent. For the OSRM process, the H2O/CH4 ratio profoundly influenced the H-2/CO ratio and the heat of the reaction. Depending on the H2O/CH4 ratio, the OSRM process could be operated in a mildly exothermic, thermoneutral or mildly endothermic mode. The CO2 conversion increased rapidly with increasing OCRM temperature and correspondingly the exothermicity of the OCRM reaction was found to decrease with increasing reaction temperature. At 900 degrees C, the OCRM reaction was mildly exothermic and provided high methane conversion and syngas selectivity. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: high temperature stable catalyst; methane; oxy-dry reforming; oxy-steam reforming; Partial oxidation

Oxy-CO2 reforming of methane to syngas over CoOx/CeO2/SA-5205 catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Energy & Fuel, 2006)
The oxy-CO2 methane reforming (OCRM) process has been investigated over the CoOx/CeO2/SA-5205 catalyst at varying reaction temperatures (750-900 degrees C), O-2/CH4 ratios (0.3- 0.45), and space velocities (20 000 - 100 000 cm(3)/g/h). With an increasing OCRM reaction temperature, the contribution from the CO2 methane reforming reaction increased while that from methane combustion reactions decreased. Correspondingly, there was an increase in the H-2/CO ratio and a sharp decrease in reaction exothermicity. At 900 C (gas hourly space velocity = 46 000 cm(3)/g/h and O-2/CH4 = 0.4), the OCRM reaction over the CoOx/CeO2/SA-5205 catalyst was mildly endothermic with > 90% CH4 conversion, > 95% H-2 selectivity, and a H-2/CO ratio of 1.63. CH4 conversion was relatively unaffected by the O-2/CH4 ratio used in the OCRM reaction; however, CO2 conversion decreased on increasing the O-2/CH4 ratio. While H-2 selectivity was not significantly affected by the O-2/CH4 ratio, the H-2/CO ratio increased linearly with an increasing O-2/CH4 ratio. The endothermicity of the reaction was found to decrease with an increasing CH4/O-2 ratio, which can be explained on the basis of increased contribution from the methane partial oxidation reaction with an increasing O-2/CH4 ratio.

Oxy-CO2 reforming of methane to syngas over CoOx/MgO/SA-5205 catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Fuel, 2006)
The OXY-CO2 methane reforming reaction (OCRM) has been investigated over CoOx supported on a MgO precoated highly macroporous silica-alumina catalyst carrier (SA-5205) at different reaction temperatures (700-900 degrees C), O-2/CH4 ratios (0.3-0.45) and space velocites (20,000-100,000cc/g/h). The reaction temperature had a profound influence on the OCRM performance over the CoO/MgO/SA-5205 catalyst; the methane conversion, CO2 conversion and H-2 selectivity increased while the H-2/CO ratio decreased markedly with increasing reaction temperature. While the O-2/CH4 ratio did not strongly affect the CH4 and CO2 conversion and H-2 selectivity, it had an intense influence on the H-2/CO ratio. The CH4 and CO2 conversion and the H-2 selectivity decreased while the H-2/CO increased with increasing space velocity. The O-2/CH4 ratio and the reaction temperature could be used to manipulate the heat of the reaction for the OCRM process. Depending on the O-2/CH4 ratio and temperature the OCRM process could be operated in a mildly exothermic, thermal neutral or mildly endothermic mode. The OCRM reaction became almost thermoneutral at an OCRM reaction temperature of 850 degrees C, O-2/CH4 ratio of 0.45 and space velocity of 46,000 cc/g/h. The CH4 conversion and H-2 selectivity over the CoO/MgO/SA-5205 catalyst corresponding to thermoneutral conditions were excellent: 95% and 97%, respectively with a H-2/CO ratio of 1.8. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: methane; oxy-CO2 reforming; Syngas

Partial oxidation of methane to syngas with or without simultaneous steam or CO2 reforming over a high-temperature stable-NiCoMgCeOx supported on zirconia-hafnia catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Applied Catalysis A-General, 2006)
A NiCoMgCeOx (Ni/Co/Mg/Ce: 1:0.2:1.2:1.2)/zirconia-hafnia catalyst with unusually high thermal stability has been investigated for syngas generation via a process that includes the catalytic partial oxidation of methane (CPOM), the oxidative steam reforming of methane (OSRM) and the oxidative CO2 reforming of methane (OCRM). The catalyst calcined at 1400 degrees C (for 4 h) showed excellent activity/selectivity for the CPOM, OSRM and the OCRM reactions; furthermore no catalyst deactivation was observed for a period of 20 h. For the CPOM process, the selectivity for H-2 was > 95% at reaction temperatures > 650 degrees C however temperatures above 800 degrees C were required to achieve > 95% CO selectivity. While the reaction temperature had a considerable influence on the CPOM product H-2/CO ratio, the space velocity (at 850 degrees C) did not affect it to any significant extent. For the OSRM process, the H2O/CH4 ratio and the reaction temperature had a strong effect on the product H-2/CO ratio and the heat of the reaction; depending on the H2O/CH4 ratio and reaction temperature, the OSRM process could be operated in a mildly exothermic, thermoneutral or mildly endothermic mode. The CO2 conversion was very strongly affected by the reaction temperature in the OCRM process; reasonably high CO2 conversion ( > 40%) could only be obtained at high OCRM reaction temperatures ( > 850 degrees C). The exothermicity of the OCRM reaction was found to decrease with increasing reaction temperature. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: dry (CO2) reforming; high-temperature stable; methane; oxy-steam reforming; Partial oxidation; Steam reforming; Syngas

Propane conversion to aromatics on highly active H-GaAlMFI: effect of thermal pretreatment - Choudhary, Tushar V.; Kinage, A.; Banerjee, S.; Choudhary, Vasant R. (Energy & Fuel, 2006)
The propane aromatization activity over H-GaAlMFI has been investigated after different thermal pretreatments ( calcination temperature range: 500- 800 degrees C) at a reaction temperature of 500 degrees C and in the space velocity range of 1500-12000 cm(3)/g/h. The calcination temperature had a strong influence on the strong acidity of the zeolite, propane conversion, and aromatic distribution. The decrease in acidity with increased thermal treatment severity correlated well with the decrease in the framework Ga. There was a considerable decrease in propane aromatization activity at calcination temperatures above 600 degrees C. The effect of calcination temperature on the propane aromatization activity can be explained in terms of change in the strong acidity of the zeolite and the extraframework Ga content. The selectivity for aromatics was found to decrease with increasing thermal pretreatment severity, while that for methane, ethane, and propylene was found to increase. The aromatic distribution was also influenced by the thermal pretreatment; the selectivity for benzene increased with increasing pretreatment temperature, while the selectivity for toluene, C-8 aromatics, and C9+ aromatics decreased.

Oxy-methane reforming over high temperature stable NiCoMgCeOx and NiCoMgOx supported on zirconia-haffnia catalysts: accelerated sulfur deactivation and regeneration - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Catalysis Communications, 2007)
NiCoMgOx and NiCoMgCeOx on commercial low surface area zirconia-haffnia catalysts have unusually high thermal stability (>= 2000 degrees C) for syngas generation via the methane partial oxidation process (J. Catal., 233, 36, 2005). Herein we report the results on accelerated sulfur deactivation (0.74 mol% sulfur in feed) and corresponding regeneration (at 800 degrees C in 1:1 O-2 + N-2 flow) over these catalysts. The NiCoMgCeOx catalyst, due to a larger mobility of lattice oxygen, showed a considerably higher resistance to sulfur poisoning; the higher mobility of the lattice oxygen in case of the NiCoMgCeOx catalyst may be related to the presence of CeO2. During the deactivation process, the selectivity for H-2 was decreased to a much greater extent than that for CO. Regeneration studies showed that even after complete deactivation of the catalysts, the original activity/selectivity of both the catalysts could be completely restored after a simple regeneration process. Based on their exceptionally high thermal stability, high activity/selectivity and easily regenerability, the NiCoMOx, and NiCoMgCeOx catalysts appear to be very promising candidates for the CPOM process. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Deactivation; high temperature stable; methane; Partial oxidation; Regeneration; Sulfur

Energy-efficient syngas production through, catalytic oxy-methane reforming reactions - Choudhary, Tushar V.; Choudhary, Vasant R. (Angewandte Chemie-International Edition, 2008)
Keywords: fuels; heterogeneous catalysis; methane activation; Partial oxidation; Syngas